2021
DOI: 10.3390/met11030509
|View full text |Cite
|
Sign up to set email alerts
|

Active Brazing of Alumina and Copper with Multicomponent Ag-Cu-Sn-Zr-Ti Filler

Abstract: The study was designed to investigate the synergic effect of Ti and Sn in the active metal brazing of Al2O3 ceramic to copper brazed, using the multicomponent Ag-Cu-Zr filler alloy. Numerous fine and hexagonal-shaped rod-like ternary intermetallic (Zr, Ti)5Sn3 phase (L/D = 5.1 ± 0.8, measured in microns) were found dispersed in the Ag-Cu matrix of Ag-18Cu-6Sn-3Zr-1Ti alloy, along with the ternary CuZrSn intermetallic phases. An approximate 15° reduction in contact angle and 3.1 °C reduction in melting point ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Cu-Sn-Ti based brazing alloys are widely used for joining materials, such as diamond/steel matrix tools [ 77 , 78 , 79 , 80 , 81 , 82 , 83 ], metal–ceramics [ 84 ], and CBN abrasive tools [ 85 , 86 , 87 ]. The most common alloys previously used for brazing were alloys based on Ag-Cu-Ti.…”
Section: Cu-sn-ti Brazing Alloysmentioning
confidence: 99%
“…Cu-Sn-Ti based brazing alloys are widely used for joining materials, such as diamond/steel matrix tools [ 77 , 78 , 79 , 80 , 81 , 82 , 83 ], metal–ceramics [ 84 ], and CBN abrasive tools [ 85 , 86 , 87 ]. The most common alloys previously used for brazing were alloys based on Ag-Cu-Ti.…”
Section: Cu-sn-ti Brazing Alloysmentioning
confidence: 99%
“…Some filler alloys, including Ag-Cu, Ag-Cu-Ti, Ag-Cu-In (or Sn)-Ti (or Zr), Cu-Sn-Ti, etc. have been successfully tested and used by various investigators experimentally to join the different metal/ceramic or ceramic/ceramic systems [2][3][4][5][6][7][8]. Active elements such as Ti, Zr, Cr, etc., can react with ceramic particles leading to a strong chemical bonding between the joint components at the joint interface.…”
Section: Introductionmentioning
confidence: 99%
“…Active elements such as Ti, Zr, Cr, etc., can react with ceramic particles leading to a strong chemical bonding between the joint components at the joint interface. Rajendran et al [3] joined the Cu to Al 2 O 3 using the active alloy Ag-18Cu-6Sn-3Zr-1T and found out that the contact angle can be reduced with the addition of Ti and Sn to Ag-Cu-Zr alloys. Silver-base active filler alloys have been widely studied by various researchers [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%